UKURAN PEMIDANAAN TERHADAP KORUPSI PENEGAK HUKUM - Abd. Rahman Saleh; Asrawi Asrawi (Fakultas Ilmu Sosial dan Humaniora, 2022)
Law enforcement is again in the public spotlight without stopping. There are various findings of cases of law enforcers who are involved in actions that should not be carried out by a law enforcer. How about law enforcers who have played the law in law enforcement, of course this is a bad act that destroys the rhythm of law enforcement. Law enforcers who are made without the guts by those who deliberately play with the law with temptations and spices to give a certain amount of money, of course, this is a disgraceful trait, and can also be qualified as a corrupt act. Why is it said to be a corrupt act, none other than because he has received gratification and or has received a number of gifts, either in the form of giving money and or also providing other facilities. That the law enforcers are the Police, Prosecutors, Advocates and Judges. The four of them are chess of law enforcement agencies who have the task of law enforcement. The task of law enforcement is to enforce the law with the existing legal rails as an inherent task for law enforcement with law enforcement standards with the dignity of the law. In this article, we will discuss the sentencing measure of law enforcement corruption.